EMBODIED COGNITION AND THE SHIFT FROM OBJECT-LIKE TO EVENT-LIKE REASONING IN MECHANICAL WAVES LEARNING: A CONCEPTUAL REVIEW WITH CRITICAL REALISM - Trisni Rofiqotun Nafisah; Muhammad Aswin Rangkuti; Yuni Warty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Physics learning in the classroom often merely focuses on writing equations and substituting numbers into formulas, while the bodily experience of how it feels for a wave to propagate is rarely truly experienced by learners. This condition is actually a legacy of the old classical cognitivism, which strictly separates the mind from the body, whereas Embodied Cognition (EC) research precisely shows the opposite: that conceptual understanding is deeply rooted in physical experiences, gestures, and interactions with the surrounding environment. This article weaves Kersting’s four dimensions of EC- physical, phenomenological, ecological, and interactionist sense- with Wittmann's framework of shifting from object-like to event-like reasoning on the topic of mechanical waves, with critical realism as an epistemological bridge explaining how cognitive mechanisms that are not directly observable can be traced through the tracks of students’ gestures and body language. Through a narrative-thematic literature review of publications themed around embodied cognition, grounded cognition, and physics conceptual reasoning, this study shows that the four dimensions of EC are intertwined in a single learning event, and that bodily experience provides the process mechanism for the reasoning shift, while Wittmann's framework becomes the conceptual marker to recognize whether that shift has actually occurred. This weaving offers a conceptual map for the design of mechanical wave learning activities that involve the bodies of learners, while simultaneously opening an empirical validation agenda through qualitative studies that trace students’ gestures and reasoning in depth.